Examining the Impact of User Experience, Electronic Word of Mouth, and Brand Trust on Purchase Intention among Generation Z Consumers of Local Skincare Products via TikTok Shop in Indonesia - Fadia Nur Rohmah; Tias Andarini Indarwati (Journal of Digital Business and Innovation Management, 2025)
This study aims to examine the influence of user experience, electronic word of mouth (eWOM), and brand trust on the purchase intention of Generation Z consumers of local skincare products via TikTok Shop in Indonesia. The “Doctor Detective” phenomenon highlights the importance of active ingredient transparency and digital reviews, with eWOM playing a key role in shaping consumer perception and trust. Within the social commerce framework of TikTok Shop, user experience includes ease of navigation, visual appeal, and emotional engagement. As active and critical digital consumers, Gen Z increasingly relies on community-based recommendations. Guided by the Theory of Planned Behavior (TPB), this research offers strategic insights for local skincare brands to enhance user experience, strengthen brand trust, and leverage eWOM to effectively drive purchase intention in the digital.